Safety-Critical Electrical Drives Topologies, Reliability, Performance - Bolvashenkov, Igor (SpringerBriefs in Electrical and Computer Engineering,, 2018)
This book focuses on one of the most important aspects of electrical propulsion systems - the creation of highly reliable safety-critical traction electrical drives. It discusses the methods and models for analysis and optimization of reliability and fault tolerance indices, based on which, it proposes and assesses methods for improving the availability, fault tolerance and performance of traction electric drives.